Changing donor funding and the challenges of integrated HIV treatment - Nattrass, N; Hodes, R; Cluver, L (American Medical Association, 2016)
Donor financing for HIV prevention and treatment has shifted from supporting disease-specific ("vertical") programs to health systems strengthening ("horizontal") programs intended to integrate all aspects of care. We examine the consequences of shifting resources from three perspectives: first, through a broad analysis of the changing policy context of health care financing; second, through an account of changing priorities for HIV treatment in South Africa; and third, through a description of some clinical consequences that the authors observed in a research study examining adherence to antiretroviral therapy (ART) and sexual health among adolescents. We note that AIDS responses are neither completely vertical nor horizontal but rather increasingly diagonal, as disease-specific protocols operate alongside integrated supply chain management, human resource development, and preventive screening. We conclude that health care programs are better conceived of as networks of policies requiring different degrees of integration into communities.